Development of Requirements for a Basic Standardized Mathematical Model of Geokhod - Aksenov V. V. Vladimir Valerievich; Beglyakov V. Yu. Vyacheslav Yurievich; Kazantsev A. A. Anton Aleksandrovich; Doroshenko I. V. (2016, 2016)
Title screen